THE MAIN THREATS TO TERRITORIAL INTEGRITY OF UKRAINE AT THE PRESENT STAGE OF STATE FORMATION (Bulletin of Kharkiv National University of Internal Affairs, 2018)
The European choice of Ukraine caused serious manifestation and realization of the threats to territorial integrity of our country. Herewith the author specifies both the real and the possible threats to territorial integrity, to which we should pay attention.It is indicated that the European choice of Ukrainian people is undeniable, but we should take into account the positions and concerns of the population of the state that does not support such a geopolitical choice to ensure the unity of the people and prevention of new national conflicts that could become a threat to territorial integrity. We need further activities of the state towards the unification of the Ukrainian people in building a European-oriented state. Ukraine can protect its «European choice» only by joint efforts.Under the threat of territorial integrity, according to the author’s opinion, we should understand the phenomenon, factor (or their combination) that make or can really make conditions or the state of full or partial impossibility of implementing the sovereignty of the Ukrainian people to be inviolable, integral territory within defined borders of Ukraine. The global task of national security of Ukraine at this stage is to ensure the territorial integrity, sovereignty, real independence and European choice of the Ukrainian people.The author of the article has singled out the following major threats to the territorial integrity of Ukraine at the present stage of state formation: invasion of Russia to some Ukrainian territories; unleashing military aggression in the East of Ukraine; information warfare against Ukraine, threats to cybersecurity and security of information resources, which actually are instruments of encroachment on the territorial integrity of Ukraine; separatism combined with terrorism as a form of its implementation. The biggest risk to national security and territorial integrity of Ukraine is, according to the author, massive support of separatist manifestations in Ukraine.